Visualization and simulation of structural dynamics of natural broad-leaved evergreen forest at Xuan Son national park - Dung, Nguyen Tien (Academia Journal of Biology, 2018)
This research was conducted at Xuan Son National Park, the data was collected on 03 permanent plots, the area of each permanent plot is 1 ha. The data collection has been conducted in the period from 2012 to 2018. The trees are classified into diameter categories of 5 cm starting from 10 cm. The structural simulation model consists of two groups of system elements including: state elements (number of trees categorized by diameter size), intermediate elements (tree density, entering and outgoing tree number of diameter categories, number of died trees of different diameter categories, number of regenerating trees). The processes of forest dynamics (regeneration of trees, change of tree number and natural death of diameter categories) were simulated through an simulation scheme in MM&S Software. The interaction is defined through regression equations: Correlation between the number of regenerating trees and the number of existing trees (R-N0), correlation between the number of diameter-category-changing trees and the number of trees at particular diameter category (Ok-Nk), correlation between the number of died trees and the number of trees at particular diameter category (Mk-Nk). The suitable regression equations (that are selected based on the results of statistic analysis) were input into the model in the simulation diagram in MM&S Software. The model in the simulation diagram has been ran, the graph was created from the results of model running to show the tendencies of the change of the tree diameter categories in time and to see the correlation between the changes of the tree diameter categories of the system. The model was exported from the simulation diagram into text file for illustration.